Problems face by Malaysian Anti-Corruption Commission (MACC) in curbing corruption: a case study in Malaysian Anti-Corruption Commission (MACC) Kelantan / Nurul Izati Mahadi and Hawa Nur Aliyah Sharol Anuar - Mahadi, Nurul Izati; Sharol Anuar, Hawa Nur Aliyah (Faculty of Administrative Science and Policy Studies, 2012)
The challenge today is different than in the past. International competition is more intense where it becoming the deciding factors in the prosperity of a country. The ability of national institutions to preserve integrity in the national administration is a critical element before a country can be regarded as implementing good governance which the main contributor to run the administration is public officials. There are two important elements that will inculcate good governance is the strengthening of democracy and the eradication of corruption. Descriptive and inferential statistic were use in order to analyze the variable in this study. Analysis is based on primary data that is survey questionnaire. The result from this analysis shows that one of the three variables is significantly correlated with the problems face by Malaysian Anti-Corruption Commission (MACC) in curbing corruption. This research is conducted to study the problems face by Malaysian Anti-Corruption Commission (MACC) in curbing corruption. It also intends to suggest the solution that can be taken in order to facing the problems arise.